PI(4,5)P2 concentration at the APC side of the Immunological Synapse is Required for Effector T cell Function - Fooksman, David Robert; Shaikh, Saame Raza; Boyle, Sarah; Edidin, Michael (East Carolina University, 2009)
Little is known about the signaling that occurs in an antigen presenting cell (APC) during contact with a T cell. Here we report the concentration of the signaling lipid, PI(4,5)P2, at the APC side of the immunological synapse. In both human and mouse cells, a PI(4,5)P2-specific fluorescent reporter, PH-GFP, detected an antigen-dependent enrichment of PI(4,5)P2 at the synapse between antigen- specific T cells and APC. When PIP(4,5)P2 was sequestered by a high concentration of PH-GFP reporter, cells were less susceptible to CTL-mediated lysis than control cells. These findings suggest a new regulatory target for modulating immune function that may be exploited for immune escape by pathogens and tumors. Originally published Journal of Immunology, Vol. 182, No. 9, May 2009
Keywords: Cytotoxicity; T cells cytotoxic; MHC; Antigen Presentation